2019
DOI: 10.1161/strokeaha.118.021558
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver-Delivered Stroke Rehabilitation in Rural China

Abstract: Background and Purpose— Stroke disability is a major health burden in rural China where rehabilitation services are inadequate. We aimed to determine the effectiveness of a novel nurse-led, caregiver-delivered model of stroke rehabilitation in rural China. Methods— A multicenter prospective, randomized open, blinded outcome assessed, controlled trial was conducted in 3 rural county hospitals in China: Zhangwu, Liaoning Province (Northeast); Qingtongxia,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
119
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(122 citation statements)
references
References 21 publications
2
119
0
1
Order By: Relevance
“…While a Cochrane Review suggested some benefits of caregivers in assisting with stroke patient exercises, 20 some caution should be exerted in light of the lack of effects from the recent ATTEND trial 21 (n=1,250) and the RECOVER trial 22 (n=246) which used family caregivers in India and China, respectively, to augment the delivery of stroke rehabilitation (e.g., mobility, self-care).…”
Section: Discussionmentioning
confidence: 99%
“…While a Cochrane Review suggested some benefits of caregivers in assisting with stroke patient exercises, 20 some caution should be exerted in light of the lack of effects from the recent ATTEND trial 21 (n=1,250) and the RECOVER trial 22 (n=246) which used family caregivers in India and China, respectively, to augment the delivery of stroke rehabilitation (e.g., mobility, self-care).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the meeting the rehabilitation needs of older adults in the rural, underserved regions of China can be particularly challenging as rehabilitation services typically are distant and/or scant and family support is increasingly absent (e.g., much of the working-age population has moved to urban, industrialized areas) [24]. Caregiver-delivered, digital-supported, and nurse-led interventions have been trialed to close the rehabilitation service gap in rural China, but more work is needed to achieve optimal results [54]. These will be important needs and gaps for China to address through future research and policy development [24,51,54,55].…”
Section: Discussionmentioning
confidence: 99%
“…Caregiver-delivered, digital-supported, and nurse-led interventions have been trialed to close the rehabilitation service gap in rural China, but more work is needed to achieve optimal results [54]. These will be important needs and gaps for China to address through future research and policy development [24,51,54,55].…”
Section: Discussionmentioning
confidence: 99%
“…Health technologies in stroke caregiving consist of different means to promote interaction using web (11-13), Information and Communication Technology (ICT) (14,15), mHealth (16)(17)(18)(19)(20)(21)(22)(23)(24), and telehealth systems (22). Web-based systems are those that are delivered through a browser on different devices such as computer, television, or mobile, with the requirement for access to the internet to use the service (11)(12)(13).…”
Section: Health Technologies In Stroke Caregivingmentioning
confidence: 99%
“…Web-based systems are those that are delivered through a browser on different devices such as computer, television, or mobile, with the requirement for access to the internet to use the service (11)(12)(13). ICT systems rely on a communication technology to connect numerous different devices (14,15), mHealth relies on mobile devices (16)(17)(18)(19)(20)(21)(22)(23)(24), and telehealth relies on telecommunication devices such as telephone to promote interaction and support (22). The intention of these systems is to promote healthcare delivery and exchange over a wider geographic distance, thereby ensuring more effective and efficient care to the person living with stroke (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24).…”
Section: Health Technologies In Stroke Caregivingmentioning
confidence: 99%